Two polypeptides associated with the ribonucleic acid polymerase core of Bacillus subtilis during sporulation. - Fukuda, R (1977)
The ribonucleic acid (RNA) polymerase from log-phase and sporulating cells of Bacillus subtilis was analyzed to determine whether any structural changes occurred during sporulation. The elution pattern of RNA polymerase from a deoxyribonucleic acid (DNA)-cellulose column revealed that sporulating cells at stages III and IV contained a new RNA polymerase fraction in addition to the vegetative holoenzyme (alpha2betabeta'sigma). Stage III cells contained the vegetative holoenzyme and a new enzyme with the composition alpha2betabeta'delta1; the molecular weight of delta1 was 28,000. Stage IV cells contained the vegetative holoenzyme, the delta1-containing enzyme, and another enzyme with the composition alpha2betabeta'delta2. The delta2 factor had a molecular weight of around 20,000. The delta-containing enzymes have a higher affinity for the DNA-cellulose column and a higher specific activity on various templates than vegetative holoenzyme. The simultaneous appearance of these enzymes with vegetative holoenzymes in sporulating cells is consistent with the data found previously with DNA-RNA hybridization studies, which showed that sporulating cells contained both vegetative and sporulation messenger RNAs.